Party politics in Portugal: municipalities and central government - Almeida, M. (2017)
Since the Portuguese revolution of April 25th, 1974, and the beginning of the democratic regime (with the first elections for parliament held on April 25th, 1975), political parties dominate the electoral process, both on central government and on the municipalities. The analysis of the political elites, their party filiations and recruitment and their social backgrounds has occupied Portuguese social scientists for the last years. With this paper, the author proposes to establish the relationship between these two levels of government, national and local, and access the importance of political parties in each of them. Many mayors’ political careers include vertical mobility, both upwards and downwards: from mayors to members of parliament to members of the European Parliament and ministers or even Prime-Minister and President of the Republic (in the case of two mayors of Lisbon), or from ministers and members of parliament to mayors. In all of these cases, their party and their position within the party has played a central role, even when some individuals have pursued other party choices in order to get re-elected, or even have presented independent candidacies (only possible since 1997).